Response of knee fibrocartilage to joint destabilization. Issue 6 (June 2015) - Dyment, N.A.; Hagiwara, Y.; Jiang, X.; Huang, J.; Adams, D.J.; Rowe, D.W.
Summary: Objective: A major challenge to understanding osteoarthritis (OA) pathology is identifying the cellular events that precede the onset of cartilage damage. The objective of this study is to determine the effect of joint destabilization on early changes to fibrocartilage in the joint. Design/Methods: The anterior cruciate ligament was transected in collagen reporter mice (Col1CFP and ColXRFP). Mineralization labels were given every 2 weeks to measure new mineralized cartilage apposition. Novel fluorescent histology of mineralized tissue was used to characterize the changes in fibrocartilage at 2 and 4 weeks post-injury. Results: Changes in fibrocartilaginous structures of the joint occur as early as 2 weeks after injury and are well developed by 4 weeks. The alterations are seen in multiple entheses and in the medial surface of the femoral and tibial condyles. In the responding entheses, mineral apposition towards the ligament midsubstance results in thickening of the mineralize fibrocartilage. These changes are associated with increases in ColX-RFP, Col1-CFP reporter activity and alkaline phosphatase enzyme activity. Mineral apposition also occurs in the fibrocartilage of the non-articular regions of the medial condyles by 2 weeks and develops into osteophytes by 4 weeks post-injury. An unexpected observation is punctate expression of tartrate resistant acid phosphatase activity in unmineralized fibrochondrocytes adjacent to active appositional mineralization. Discussion: These observations suggest that fibrocartilage activates prior to degradation of the articular cartilage. Thus clinical and histological imaging of fibrocartilage may be an earlier indicator of disease initiation and may indicate a more appropriate time to start preventative treatment.